Impact of warm-up methods on strength-speed for sprinters in athletics: a mini review - Herrera, E.; Osorio-Fuentealba, C. (Frontiers in Sports and Active Living, 2024)
In athletics, achieving peak performance during competitions is crucial. Warm-up strategies play a crucial role in optimizing the strength-speed performance of sprinters in athletics, especially tailored to the physiological demands of speed events. The need to balance flexibility, prevent injuries, and enhance power output makes the selection of an effective warm-up protocol essential. This narrative review examines different warm-up methods used by athletes and their effects on strength-speed in sprinters in athletics. The main findings indicate that Foam Rolling (FR), Isometric Exercises and Pre-Competitive Massages have no significant effects on sprint performance. Static stretching and prolonged Pre-Competitive Massages have negative impacts on strength and power. The Vibration Platform enhances step length, step rate and running velocity, jump height and total number of jumps performed in a 30-s period in non-experienced sprinters. Eccentric Exercise increases vertical force, Post-Activation Potentiation (PAP) demonstrates a reduction in 100-meter time and short-term improvement in vertical and horizontal jumps. Blood Flow Restriction (BFR) significantly improving jump height and flight time. Various warm-up methods have been identified, some focusing on flexibility, others potentially detrimental, and some enhancing strength and power. Implementing effective warm-ups, particularly those promoting strength and power, poses a challenge for coaches seeking reliable alternatives to boost performance.